Análisis de los costos de venta para determinar la rentabilidad de la tienda DOSMIL, del barrio Luis R. Calvo de la ciudad de Santa Marta (2024)
In the context of the field of study Antonio Nariño University, there has been a growing interest in this research topic (Analysis of the cost of sales to determine the profitability of the DOSMIL store in the neighborhood Luis R. Calvo in the city of Santa Marta), however there is a significant problem related to the following question: How can a detailed analysis of the cost of sales in the DOSMIL store, located in the neighborhood Luis R. Calvo in the city of Santa Marta, to evaluate its profitability and make strategic decisions to promote its growth and sustainability in the local market?This question arose due to the current problem of identifying whether it is really getting a profitability after deducting all costs and expenses and thus avoid losses, therefore this analysis in addition to benefiting the owner of the DOSMIL store will also bring benefits to the residents of the sector, as this will help to provide fair and affordable prices. Thus, the main objective of this project is to show the results through a detailed daily, monthly and annual analysis, which will help to make better decisions and implement strategies that lead to achieve the purpose.